THE EFFECTIVENESS OF APPLICATION OF ENGLISH SONG TO IMPROVE LANGUAGE LEARNING ENGLISH SIXTH GRADE ELEMENTARY SCHOOL (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
There is a lack of desire to learn English. Reading, writing, and speaking English is limited. For students, the lack of strategic application of information is attractive in the classroom. The aim of the study was to improve sixth graders' English language learning by using English songs at Mekarsari Elementary School. Students' reactions to the use of English songs to help students learn English to conduct quasi-experimental or pseudo experiments, the study used quantitative methods. It is forbidden for researchers to change their subject. The experimental and control groups in the study were identified using random groupings. The findings of this study reveal that song media can help learners improve their English language skills. Students who are taught using music media perform better than students who are taught using conventional media. The use of song media in English learning in the sixth graders of Mekarsari Elementary School is more effective than the use of traditional media. This is shown by a significant difference in the improvement of English language learning of sixth graders of Mekarsari Elementary School who are taught using song media against those who are taught using conventional media.
Keywords: Students; Language development; Control groups; Song